Nitrogen-containing graphdiyne, preparation method thereof and application of nitrogen-containing graphdiyne in lithium battery diaphragm

Through a new preparation method, nitrogen atoms are introduced to form nitrogen-containing graphite alkynes and applied to lithium battery separators, solving the problems of electrochemical interface instability and lithium dendrites penetration, significantly improving the performance and safety of the battery.

CN119797355APending Publication Date: 2025-04-11LIANYUNGANG NORMAL COLLEGE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510019472.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When graphiteyne is applied to lithium battery separators, there is an instability of the electrochemical interface, making it difficult to maintain a full carbon network and a uniform sub-nanopore structure, resulting in lithium dendrites penetration and diaphragm damage.

Method used

By a preparation method, it includes passing acetylene gas into a saturated cuprous chloride solution, filtration and washing to obtain hydrated acetylene copper, then reacting with hexabromobenzene and tetrakis(triphenylphosphine)palladium to form graphyne, and introducing nitrogen atoms through reaction with melamine to form nitrogen-containing graphyne.

Benefits of technology

The nitrogen-containing graphiteyne produced significantly improves ion transport performance, electrochemical stability, mechanical properties and cycle stability in the lithium battery separator, extends the cycle life of the battery and improves safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005230882120000101
    Figure BDA0005230882120000101
  • Figure BDA0005230882120000111
    Figure BDA0005230882120000111
Patent Text Reader

Abstract

The invention relates to the technical field of lithium battery diaphragms, in particular to nitrogen-containing graphdiyne, a preparation method thereof and application of the nitrogen-containing graphdiyne in a lithium battery diaphragm. The method comprises the following steps: S1, introducing acetylene gas into a cuprous chloride ammonia saturated solution, reacting, filtering, washing and drying to obtain hydrated acetylene copper; s2, mixing acetylene copper hydrate, hexabromo-benzene and tetrakis (triphenylphosphine) palladium, after reaction, dipping, filtering, washing and drying to obtain a solid-phase substance, and then heating the solid-phase substance for reaction under the protection of nitrogen to obtain graphdiyne; s3, grinding and sieving graphdiyne, mixing with melamine, heating to react, washing and drying to obtain the nitrogen-containing graphdiyne. When the nitrogen-containing graphdiyne provided by the invention is applied to a lithium battery diaphragm, a lithium ion battery has a relatively low attenuation rate and a relatively high cycle capacity retention rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery separators, and in particular relates to nitrogen-containing graphyne, a preparation method thereof, and application thereof in lithium battery separators. Background Art

[0002] At present, the development of new functional separators with stable structure, uniform pores, excellent conductivity and rich active sites for lithium batteries can effectively inhibit the growth of lithium dendrites. Graphdyne (GDY) is a new two-dimensional carbon allotrope with coexisting sp1 and sp2 hybridized carbon atoms. It has a large conjugated system and is different from graphene with a regular hexagonal lattice. It has many advantages. There are abundant molecular pores in the GDY layered structure. In addition, the excellent growth controllability and chemical stability bring good rate performance and ultra-long cycle life to lithium batteries. However, when GDY is functionalized as a battery separator, there is electrochemical interface instability, and how to maintain a full carbon network and uniform sub-nanometer pore structure remains a challenge.

[0003] For example, CN117208894A relates to a method for preparing graphdiyne from acetylene gas. Specifically, an excess of cuprous chloride is dissolved in an aqueous ammonia solution to obtain a saturated cuprous chloride solution; 10-30 g of calcium carbide is put into a gas collecting bottle, and an excess of saturated saline is added dropwise to generate acetylene gas, and the acetylene gas is passed into the saturated cuprous chloride solution to obtain a cuprous chloride ammonia solution; the cuprous chloride ammonia solution is washed with deionized water and anhydrous ethanol, and dried to obtain acetylene copper hydrate; 1-8 g of acetylene copper hydrate, 1.10 4-2.208g hexabromobenzene and 0.1-1g palladium catalyst are added to an organic mixed solvent to obtain a liquid mixture; the liquid mixture is stirred and reacted at 70°C for 48h to obtain a graphene diyne slurry; the graphene diyne slurry is rotary evaporated to obtain a graphene diyne viscous material, 10-0mL concentrated hydrochloric acid and 40-100mL water are added to the graphene diyne viscous material and soaked for 0.5-3h, washed and dried, and heated to 400°C at a rate of 5°C / min in a nitrogen atmosphere and calcined for 2h to obtain graphene diyne. Although this method obtains well-structured graphene, the full carbon network and uniform sub-nanometer pore structure of graphene cannot be maintained when applied to lithium battery separators.

[0004] For example, CN114094277A discloses a lithium-ion battery Graphene coated diaphragm and a preparation method thereof, wherein the diaphragm comprises a base film and a coating layer coated on the base film; the coating layer comprises a Graphene coating and a polyvinylidene fluoride coating coated on the Graphene coating; the base film is one of a polyolefin film, a non-woven fabric film, and a polyimide film, and the Graphene coating is made of the following raw materials in weight percentage: Graphene 98%-98.8%, a first dispersant 0.2%-0.6%, a first thickener 0.4%-0.7%, a first binder 0.5%-1%, and a first wetting agent 0.05%-0.2%. Graphene is added to the application, and the added Graphene is beneficial to improving the ionic conductivity of the battery and accelerating the transmission efficiency of lithium ions, thereby improving the rate performance of the lithium-ion battery. However, the Graphene in the application is not modified, and the resulting diaphragm cannot inhibit the penetration of lithium dendrites, which will eventually destroy the Graphene.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a nitrogen-containing graphyne and a preparation method thereof and an application in a lithium battery separator. The nitrogen-containing graphyne provided by the present invention, when applied to a lithium battery separator, enables a lithium-ion battery to have a lower attenuation rate and a higher cycle capacity retention rate.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] In a first aspect, an embodiment of the present invention provides a method for preparing nitrogen-containing graphyne, comprising the following steps:

[0009] S1, passing acetylene gas into a saturated solution of cuprous chloride and ammonium, and filtering, washing and drying after the reaction to obtain hydrated acetylene copper;

[0010] S2, mixing hydrated copper acetylide, hexabromobenzene and tetrakis(triphenylphosphine)palladium, and after the reaction, immersing, filtering, washing and drying to obtain a solid phase, and then heating the solid phase under nitrogen protection to react to obtain graphyne;

[0011] S3, grinding and sieving the graphyne, mixing it with melamine, heating for reaction, washing and drying to obtain nitrogen-containing graphyne.

[0012] In a preferred embodiment, in step S2, the mass ratio of hydrated copper acetylide, hexabromobenzene and tetrakis(triphenylphosphine)palladium is 2:(0.5-1.5):(0.3-1).

[0013] In a preferred embodiment, in step S2, the specific conditions of the reaction are: reflux reaction at 50-100°C for 24-72h, and then concentration to dryness at 40°C-80°C.

[0014] In a preferred embodiment, in step S2, the solvent used for the impregnation is a mixture of concentrated hydrochloric acid and deionized water, the mass ratio of the solvent to the hydrated copper acetylide is (50-200):2, and the volume ratio of the concentrated hydrochloric acid to deionized water is 2:(4-10).

[0015] In a preferred embodiment, in step S2, the immersion time is 1-4 hours.

[0016] In a preferred embodiment, in step S2, the heating reaction conditions are: temperature 300°C-500°C, time 20-30h.

[0017] In a preferred embodiment, in step S3, the sieve used for screening is 200-500 mesh.

[0018] In a preferred embodiment, in step S3, the mass ratio of graphyne to melamine is 1:(10-20).

[0019] In a preferred embodiment, in step S3, the specific conditions of the heating reaction are: heating at 700° C.-1000° C. for 2-6 h under argon atmosphere.

[0020] In the present invention, in toluene containing tetrakis(triphenylphosphine)palladium, the halogenated group on the benzene ring is activated to form Ph-Pd-Br. Then, Ph-Pd-Br reacts with copper acetylene in pyridine to generate CuBr and Ph-Pd-C≡C-Cu. During the reaction, pyridine forms a coordination bond with Pd to stabilize the reaction product. Due to the instability of C-Pd-C, it breaks and generates Ph-Pd-C≡C-Cu. During the reaction, the Pd atom loses a carbon atom and forms a new bond with Cu. Then C-Cu undergoes a coupling reaction to generate Ph-C≡CC≡C-Ph. The raw material of graphyne doped with nitrogen anchors the azide to the graphyne acetylenic bond, and then obtains N-doped graphyne through a cyclization reaction.

[0021] The nitrogen-containing graphyne prepared by the present invention can effectively improve the ion transmission performance, improve the electrochemical stability, enhance the mechanical properties of the diaphragm, increase the active sites, improve the wettability of the electrolyte and improve the safety of the battery when applied to the lithium battery diaphragm.

[0022] Specifically, the introduction of nitrogen atoms will change the electronic structure of graphyne, making its surface charge distribution more uneven, thereby enhancing the adsorption and affinity for lithium ions, accelerating the transmission speed of lithium ions in the diaphragm, and improving the charging and discharging efficiency of the battery; nitrogen-modified graphyne has better chemical stability and antioxidant properties, can maintain a stable structure and performance during the long-term charging and discharging process of lithium batteries, reduce battery performance degradation caused by side reactions between electrode materials and electrolytes, and extend the cycle life of the battery; nitrogen modification can enhance the interaction between graphyne and other diaphragm materials to a certain extent, making the overall structure of the diaphragm more stable, improving its mechanical strength such as tensile strength and puncture resistance, preventing the diaphragm from breaking or being damaged due to external forces during the use of the battery, and ensuring the safety of the battery; the introduction of nitrogen atoms can increase the active sites of graphyne, these active sites can interact with lithium ions in the electrolyte, and promote the migration and diffusion of lithium ions. In addition, the active sites can also improve the membrane's adsorption capacity for impurities such as polysulfides, reduce the deposition of impurities on the electrode surface, and further improve the performance of the battery; the surface properties of nitrogen-modified graphyne change, improving its wettability to the electrolyte, allowing the electrolyte to better penetrate into the pores of the diaphragm and fully fill the channels inside the diaphragm, thereby reducing the internal resistance of the battery and improving the battery's high-current charge and discharge performance; in addition, the use of nitrogen-modified graphyne can improve the thermal stability of the diaphragm, making it less likely to deform or melt in a high-temperature environment, reducing the risk of thermal runaway of the battery, and good ion transport performance and inhibition of lithium dendrite growth can also reduce the possibility of internal short circuits in the battery and improve the safety of battery use. The introduction of nitrogen atoms enables graphyne to stabilize the structure of the electrode material and inhibit the growth of lithium dendrites, but the inhibition limit is limited, and there is still a risk of puncture after long-term use.

[0023] In a second aspect, the present invention provides nitrogen-containing graphyne obtained by the above-mentioned preparation method of nitrogen-containing graphyne.

[0024] In a third aspect, the present invention provides the use of the nitrogen-containing graphyne in a lithium battery separator as described above, wherein the separator comprises:

[0025] Basement membrane;

[0026] and a functional coating applied on the base film;

[0027] The functional coating comprises nitrogen-containing graphyne and modified nano metal particles, and the modified nano metal particles are obtained by modifying nano silicon dioxide and nano titanium dioxide with polyaniline.

[0028] In a preferred embodiment, the mass ratio of the nitrogen-containing graphyne to the modified nano-metal ions is 100:(1-10).

[0029] In a preferred embodiment, the mass ratio of the nano-silicon dioxide to the nano-titanium dioxide is (1-3): (1-3).

[0030] In a preferred embodiment, the preparation method of the modified nano metal ions is as follows:

[0031] Aniline, surfactant and water are mixed and the pH is adjusted to 2-4, then nano silicon dioxide and nano titanium dioxide are added and dispersed evenly, then an initiator is added dropwise, the reaction is stirred, and the modified nano metal ions are obtained by centrifugal filtration and drying.

[0032] The present invention produces polyaniline in situ on nano-silicon dioxide and nano-titanium dioxide to obtain polyaniline-modified nano-metal particles. When the nitrogen-containing graphyne and modified nano-metal particles obtained by the present invention are coated on a base film, the ionic conductivity can be effectively improved, the mechanical properties of the diaphragm can be enhanced, the thermal stability of the battery can be improved, and the cycle stability of the battery can be enhanced.

[0033] In terms of improving ion conductivity, polyaniline has good electrical conductivity. When coated on the surface of nano-silicon dioxide and nano-titanium dioxide, it can form a conductive network and improve the overall electronic transmission capacity of the material. Nano-silicon dioxide and nano-titanium dioxide themselves also have certain electronic conductivity. When combined with polyaniline, they can further enhance the effect of this conductive network and provide more channels and faster transmission rates for the transmission of lithium ions. Nitrogen-containing Graphene has a unique two-dimensional planar structure and good electrical properties. Its large conjugated system is conducive to the delocalization and conduction of electrons. In lithium battery separators, nitrogen-containing Graphene can provide fast lithium ion transmission channels. At the same time, its own conductivity also helps to improve the overall ion conductivity of the separator, thereby accelerating the battery's charge and discharge speed and improving the battery's rate performance. When they work together, they can form a more complete three-dimensional conductive network, greatly improving the transmission efficiency of lithium ions in the separator, so that the battery can still maintain good charge and discharge performance at high current density and reduce the occurrence of battery polarization.

[0034] In terms of enhancing the mechanical properties of the diaphragm, nano-silicon dioxide and nano-titanium dioxide have high hardness and strength, which can enhance the mechanical stability of the diaphragm. Polyaniline coated on its surface can improve the compatibility and bonding between nanoparticles and the diaphragm matrix, so that the nanoparticles can be better dispersed in the diaphragm, thereby more effectively improving the tensile strength, puncture strength and other mechanical properties of the diaphragm, and preventing the diaphragm from breaking due to stress during the battery charging and discharging process. Nitrogen-containing graphyne has good flexibility and mechanical strength, and its two-dimensional sheet structure can play a role in strengthening the skeleton in the diaphragm, improve the diaphragm's tensile and tearing resistance, and enable the diaphragm to better withstand the pressure changes inside the battery and the volume expansion of the electrode material. When working together, it can enhance the mechanical properties of the lithium battery diaphragm from different dimensions, so that the diaphragm has higher strength and better flexibility, effectively extending the battery cycle life, and improving the safety and stability of the battery.

[0035] In terms of improving the thermal stability of batteries, nano-silicon dioxide and nano-titanium dioxide have high thermal stability and can improve the heat resistance of the diaphragm to a certain extent. Polyaniline also has good stability at high temperatures, and its coating layer can prevent the agglomeration of nanoparticles at high temperatures, maintaining the stability of the material's performance, so that the diaphragm can still maintain good ion conductivity and mechanical properties under high temperature environments. Nitrogen-containing graphyne itself has excellent chemical stability and thermal stability, and it is not easy to decompose or change its structure at high temperatures. In lithium battery diaphragms, nitrogen-containing graphyne can improve the thermal stability of the diaphragm, reduce the thermal shrinkage of the diaphragm at high temperatures, prevent the diaphragm from melting, rupture and other problems in high temperature environments, ensure the normal operation of the battery, and can significantly improve the thermal stability of lithium battery diaphragms when used together, so that the battery has better safety and reliability under high temperature conditions, and reduce the battery performance degradation and safety accidents caused by high temperature.

[0036] In improving the cycle stability of the battery, the presence of polyaniline can alleviate the volume change of nano-silicon dioxide and nano-titanium dioxide during the charge and discharge process, reduce the material pulverization and shedding caused by volume expansion and contraction, and improve the structural stability of the electrode material. At the same time, the conductive properties of polyaniline help to maintain good electrical contact between the electrode materials, thereby improving the cycle stability of the battery, and the two metal particles have a good barrier effect, which can inhibit the penetration of lithium dendrites. With the ion sieving effect of graphyne, the two collaborate to further optimize the lithium ion transmission path, screen ions of suitable particle size to pass, and improve battery safety and charge and discharge efficiency. In fact, nitrogen-containing graphyne can stabilize the structure of the electrode material and inhibit the growth of lithium dendrites. During the battery charge and discharge process, the growth of lithium dendrites can easily puncture the diaphragm, causing internal short circuits in the battery and reducing the cycle life of the battery. Nitrogen-containing graphyne can effectively block the growth of lithium dendrites and protect the integrity of the diaphragm through its special structure and properties, thereby improving the cycle stability of the battery. When working together, they complement each other in inhibiting the growth of lithium dendrites, and can improve the cycle stability of the battery from multiple aspects, reduce the capacity decay of the battery during the cycle, extend the service life of the battery, and improve the overall performance and economy of the battery.

[0037] In a preferred embodiment, the mass ratio of the aniline, surfactant, water, nano-silicon dioxide, nano-titanium dioxide and initiator is 1:(0.8-1.5):(40-100):(1-3):(1-3):(1-4).

[0038] In a preferred embodiment, the surfactant is one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium oleate, triethanolamine or sodium hexametaphosphate.

[0039] In a preferred embodiment, the initiator is ammonium persulfate or potassium persulfate.

[0040] In a preferred embodiment, the stirring reaction time is 2-4 hours, and the stirring reaction temperature is 60°C-90°C.

[0041] In a preferred embodiment, the particle size of the nano-silicon dioxide is 50-100 nm.

[0042] In a preferred embodiment, the particle size of the nano titanium dioxide is 50-100 nm.

[0043] In a preferred embodiment, the base film is one or more of a polyolefin film, a non-woven fabric film, and a polyimide film.

[0044] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0045] 1. The nitrogen-containing graphyne prepared by the present invention can effectively improve the ion transmission performance, improve the electrochemical stability, enhance the mechanical properties of the diaphragm, increase the active sites, improve the wettability of the electrolyte and improve the safety of the battery when applied to the lithium battery diaphragm.

[0046] 2. The nitrogen-containing graphyne and modified nano-metal particles obtained by the present invention, when coated on a base film, can effectively improve ionic conductivity, enhance the mechanical properties of the diaphragm, improve the thermal stability of the battery and enhance the cycle stability of the battery. DETAILED DESCRIPTION

[0047] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] Unless otherwise specified, the reagents and raw materials used in the present invention are commercially available.

[0049] Nano-silicon dioxide, with an average particle size of 60 nm, was purchased from Shanghai Chaodian Nanotechnology Co., Ltd.

[0050] Nano-titanium dioxide, with an average particle size of 60 nm, was purchased from Jiangsu Hushen Titanium Dioxide Technology Co., Ltd.

[0051] Example 1

[0052] This embodiment provides a method for preparing a lithium battery separator, comprising the following steps:

[0053] S1, passing acetylene gas into a saturated solution of cuprous chloride and ammonium, and filtering, washing and drying after the reaction to obtain hydrated acetylene copper;

[0054] S2, by weight, 2 parts of hydrated acetylene copper, 1 part of hexabromobenzene and 0.5 parts of tetrakis(triphenylphosphine)palladium are mixed, refluxed at 70°C for 48 hours, then concentrated to dryness at 60°C, then immersed in a mixture of 20 parts of concentrated hydrochloric acid and 80 parts of deionized water for 2 hours, filtered, washed and dried to obtain a solid phase, and then the solid phase is kept at 400°C for 240 hours under nitrogen protection to obtain graphyne;

[0055] S3, by mass, 1 part of graphyne was ground through a 200-mesh sieve and then mixed with 15 parts of melamine, heated at 800° C. for 4 h in an argon atmosphere, washed and dried to obtain nitrogen-containing graphyne.

[0056] S4, attaching nitrogen-containing graphyne to a polyolefin film base film to obtain.

[0057] Example 2

[0058] This embodiment provides a method for preparing a lithium battery separator, comprising the following steps:

[0059] S1, passing acetylene gas into a saturated solution of cuprous chloride and ammonium, and filtering, washing and drying after the reaction to obtain hydrated acetylene copper;

[0060] S2, by weight, 2 parts of hydrated acetylene copper, 1 part of hexabromobenzene and 0.5 parts of tetrakis(triphenylphosphine)palladium are mixed, refluxed at 70°C for 48 hours, then concentrated to dryness at 60°C, then immersed in a mixture of 20 parts of concentrated hydrochloric acid and 80 parts of deionized water for 2 hours, filtered, washed and dried to obtain a solid phase, and then the solid phase is kept at 400°C for 240 hours under nitrogen protection to obtain graphyne;

[0061] S3, by mass, 1 part of graphyne was ground through a 200-mesh sieve and then mixed with 15 parts of melamine, heated at 800° C. for 4 h in an argon atmosphere, washed and dried to obtain nitrogen-containing graphyne.

[0062] S4, by mass, 1 part of aniline, 1 part of sodium dodecyl sulfate, and 80 parts of water were mixed and the pH was adjusted to 3, then 2 parts of nano-silicon dioxide with an average particle size of 60 nm and 2 parts of nano-titanium dioxide with an average particle size of 60 nm were added and dispersed evenly, then 3 parts of ammonium persulfate were added dropwise, and the reaction was stirred. The reaction temperature was 70°C, the reaction time was 3 hours, and the modified nano-metal ions were obtained by centrifugation filtration and drying.

[0063] S5, mixing nitrogen-containing graphyne and modified nano-metal ions in a mass ratio of 10:7 and attaching the mixture to a polyolefin film base film to obtain a product.

[0064] Comparative Example 1

[0065] The difference between this comparative example and Example 1 is that step S3 is not performed, that is, graphyne is not modified.

[0066] Comparative Example 2

[0067] The difference between this comparative example and Example 2 is that step S3 is not performed, that is, graphyne is not modified.

[0068] Comparative Example 3

[0069] The difference between this comparative example and Example 2 is that step S4 is changed to:

[0070] S4, by mass, 1 part of aniline, 1 part of sodium dodecyl sulfate, and 80 parts of water were mixed and the pH was adjusted to 3, then 4 parts of nano-silicon dioxide with an average particle size of 60 nm were added and dispersed evenly, then 3 parts of ammonium persulfate were added dropwise, stirred for reaction, the reaction temperature was 70°C, the reaction time was 3h, and the modified nano-metal ions were obtained by centrifugal filtration and drying.

[0071] Comparative Example 4

[0072] The difference between this comparative example and Example 2 is that step S4 is changed to:

[0073] S4, by mass, 1 part of aniline, 1 part of sodium dodecyl sulfate, and 80 parts of water were mixed and the pH was adjusted to 3, then 4 parts of nano titanium dioxide with an average particle size of 60 nm were added and dispersed evenly, then 3 parts of ammonium persulfate were added dropwise, stirred for reaction, the reaction temperature was 70°C, the reaction time was 3 hours, and the modified nano metal ions were obtained by centrifugation filtration and drying.

[0074] Comparative Example 5

[0075] The difference between this comparative example and Example 2 is that step S4 and step S5 are changed to:

[0076] The nitrogen-containing graphyne, nano silicon dioxide with an average particle size of 60 nm, and nano titanium dioxide with an average particle size of 60 nm are mixed in a mass ratio of 10:3.5:3.5 and attached to a polyolefin film base film to obtain a product.

[0077] Comparative Example 6

[0078] The difference between this comparative example and Example 2 is that the 2 parts of nano-silicon dioxide with an average particle size of 60 nm and the 2 parts of nano-titanium dioxide with an average particle size of 60 nm in step S4 are replaced by 4 parts of nano-aluminum oxide with an average particle size of 60 nm.

[0079] Performance Testing

[0080] 1. Ionic conductivity: The diaphragms obtained in the examples and comparative examples were tested on an electrochemical workstation, and the data were recorded and the ionic conductivity was calculated. The results are shown in Table 1.

[0081] 2. Electrochemical performance test: The membrane-assembled batteries obtained in the examples and comparative examples were subjected to constant current charge-discharge cycle tests at currents of 1C and 5C, and their electrochemical performances were measured and calculated. The results are shown in Table 1.

[0082] Table 1 Performance test results

[0083]

[0084]

[0085] It can be seen from the above performance test results that the separators of Examples 1-2 enable the lithium-ion batteries to have a lower attenuation rate and a higher cycle capacity retention rate, especially the comprehensive performance of Example 2 is the most outstanding, which is mainly due to the synergistic effect of nitrogen-containing graphyne and modified nanometal particles.

[0086] The comparative example does not adopt the necessary technical solution, resulting in its performance being significantly worse than that of the embodiment in the corresponding performance test. This better proves the irreplaceable nature of the specific technical solution of the present application in achieving technical effects and solving technical problems.

[0087] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing nitrogen-containing graphyne, characterized in that: The following steps are involved: S1, passing acetylene gas into a saturated solution of cuprous chloride and ammonium, and filtering, washing and drying after the reaction to obtain hydrated acetylene copper; S2, mixing hydrated copper acetylide, hexabromobenzene and tetrakis(triphenylphosphine)palladium, and after the reaction, immersing, filtering, washing and drying to obtain a solid phase, and then heating the solid phase under nitrogen protection to react to obtain graphyne; S3, grinding and sieving the graphyne, mixing it with melamine, heating for reaction, washing and drying to obtain nitrogen-containing graphyne.

2. The method for preparing nitrogen-containing graphyne according to claim 1, characterized in that: In step S2, the mass ratio of hydrated copper acetylide, hexabromobenzene and tetrakis(triphenylphosphine)palladium is 2:(0.5-1.5):(0.3-1); And / or, in step S2, the specific conditions of the reaction are: reflux reaction at 50-100° C. for 24-72 hours, and then concentration to dryness at 40° C.-80° C.; And / or, in step S2, the solvent used for the impregnation is a mixture of concentrated hydrochloric acid and deionized water, the mass ratio of the solvent to the hydrated copper acetylide is (50-200):2, and the volume ratio of the concentrated hydrochloric acid to the deionized water is 2:(4-10); And / or, in step S2, the immersion time is 1-4h; And / or, in step S2, the heating reaction conditions are: temperature 300°C-500°C, time 20-30h.

3. The method for preparing nitrogen-containing graphyne according to claim 1, characterized in that: In step S3, the sieve used for sieving is 200-500 mesh; And / or, in step S3, the mass ratio of graphyne to melamine is 1:(10-20); And / or, in step S3, the specific conditions of the heating reaction are: heating at 700° C.-1000° C. for 2-6 hours under argon atmosphere.

4. A nitrogen-containing graphyne obtained by the method for preparing nitrogen-containing graphyne according to any one of claims 1 to 3.

5. A use of nitrogen-containing graphyne as claimed in claim 4 in a lithium battery separator, characterized in that: The diaphragm comprises: Basement membrane; and a functional coating applied on the base film; The functional coating comprises nitrogen-containing graphyne and modified nano metal particles, and the modified nano metal particles are obtained by modifying nano silicon dioxide and nano titanium dioxide with polyaniline.

6. The use of nitrogen-containing graphyne in a lithium battery separator according to claim 5, characterized in that: The mass ratio of the nitrogen-containing graphyne to the modified nano-metal ion is 100:(1-10); And / or, the mass ratio of the nano-silicon dioxide to the nano-titanium dioxide is (1-3): (1-3).

7. The use of nitrogen-containing graphyne in a lithium battery separator according to claim 5, characterized in that: The preparation method of the modified nano metal ion is as follows: Aniline, surfactant and water are mixed and the pH is adjusted to 2-4, then nano silicon dioxide and nano titanium dioxide are added and dispersed evenly, then an initiator is added dropwise, the reaction is stirred, and the modified nano metal ions are obtained by centrifugal filtration and drying.

8. The use of nitrogen-containing graphyne in a lithium battery separator according to claim 7, characterized in that: The mass ratio of aniline, surfactant, water, nano-silicon dioxide, nano-titanium dioxide and initiator is 1:(0.8-1.5):(40-100):(1-3):(1-3):(1-4); And / or, the surfactant is one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium oleate, triethanolamine or sodium hexametaphosphate; And / or, the initiator is ammonium persulfate or potassium persulfate.

9. The use of nitrogen-containing graphyne in a lithium battery separator according to claim 7, characterized in that: The stirring reaction time is 2-4h, and the stirring reaction temperature is 60°C-90°C; And / or, the particle size of the nano-silicon dioxide is 50-100 nm; And / or, the particle size of the nano titanium dioxide is 50-100 nm.

10. The use of nitrogen-containing graphyne in a lithium battery separator according to claim 5, characterized in that: The base film is one or more of a polyolefin film, a non-woven fabric film, and a polyimide film.

Citation Information

Patent Citations

  • Graphdiyne coated diaphragm of lithium ion battery and preparation method of graphdiyne coated diaphragm

    CN114094277A

  • Method for preparing graphite diyne from acetylene gas

    CN117208894A